Effects and molecular mechanism of endophytic elicitors on the accumulation of secondary metabolites in medicinal plants - Wang, Yaxuan; Chen, Nana; Deng, Kuanping; Zhong, Xinying; Li, Zhaogao; Li, Lin; Xu, Delin (Frontiers in Microbiology, 2025)
Endophytes in medicinal plants possess significant biological value since they have in them the ability to provide elicitors crucial in regulating plant growth as also different secondary metabolites. This review emphasizes the effective ability of endophytic fungi to induce their hosts, explains the biological mechanisms of using endophytic fungi to enhance the accumulation of secondary metabolites in medicinal plant cultures, and summarizes the extensive application of endophytic fungi elicitors in medicinal plant cultivation. The main goal of this article is to clarify the mechanism and important role of endophytic elicitors in the production of natural drugs. This information will be helpful for scientific researchers in controlling the quality of medicinal materials, prioritizing endophytic resources, and achieving a circular and sustainable development and production of natural medicine.